Development and Verification of Potassium Determination Method in Solid NPK Fertilizer by Atomic Absorption Spectrophotometry - Ni’mahv, Latifatun; Catur Rini Widyastuti; Rahimsyah ljas Nur Rasyid (Universitas Negeri Semarang, 2022)
The measurement of potassium levels in solid NPK fertilizer using the K₂O digestion method still requires repeatability to ensure the validity of the measurement results. This study aims to develop and validate a method for determining potassium levels using the P₂O₅ digestion method in accordance with SNI 2803:2012, employing a pragmatic approach based on SNI 7763:2018. Potassium analysis was performed using an Atomic Absorption Spectrophotometer (AAS) with several validation parameters. The potassium levels measured using both the K₂O and P₂O₅ digestion methods were 14%. The method demonstrated linearity, with a correlation coefficient (r²) of 0.9986. The precision values for the K₂O and P₂O₅ digestion methods, based on Relative Standard Deviation (%RSD) < 2/3 CV Horwitz, were 1.6% < 1.8% and 1.1% < 1.8%, respectively, while t-calculated (0.646) < t-tabulated (2.179). Accuracy, as indicated by the percentage recovery for the K₂O and P₂O₅ digestion methods, was 108% and 101%, respectively. The P₂O₅ digestion method is categorized as an accurate, precise, and efficient technique for determining potassium levels in solid NPK fertilizer samples, particularly in large quantities